Problem Filosofis Pengembangan Kurikulum Pendidikan - Ahmad Samawi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
Developing curriculum for education faces philosophical problems when improvement of education quality is related to the curriculum coverage, the method of curriculum development, and the benefits of the curriculum. This article describes the philosophical problems in developing curriculum for education. The problems include how the curriculum sees human beings, how the curriculum is implemented, and what benefits education can offer.